Menumbuhkan Jiwa Kewirausahaan Untuk Meningkatkan Minat Dan Motivasi Siswa Smks 1 Pembangunan Kota Bengkulu - Irwanto, Tito; Nasution, Suswati; Yanti, Rina Trisna; Rahmi, Fathur (Universitas Dehasen Bengkulu, 2024)
Entrepreneurship education at the secondary education level, especially at Vocational High Schools (SMK), has an important role in forming a generation that is able to face the challenges of the modern economy. This education not only prepares students with technical knowledge, but also explores the creative and innovative potential needed in the business world. Entrepreneurship education plays an important role in increasing entrepreneurial motivation and innovation in vocational school students. High motivation is considered the key to success in running a business, while innovation opens up opportunities to face business competition in a unique and effective way. This service was carried out at SMKS 1 for the development of the city of Bengkulu on Friday 7 June 2024. The implementation of this service activity was to carry out socialization about cultivating an entrepreneurial spirit to increase student interest and motivation, where during the socialization there was a question and answer discussion with the students of SMKS 1 for the Development of the city of Bengkulu. This socialization aims to foster an entrepreneurial spirit in students and increase the motivational interest of students at SMKS 1 for the development of Bengkulu City. It is very influential in improving the entrepreneurial spirit from an early age, and increasing relationships and network connections is necessary.